2018
DOI: 10.1080/00949655.2018.1430801
|View full text |Cite
|
Sign up to set email alerts
|

A beta-inflated mean regression model with mixed effects for fractional response variables

Abstract: ResumenEn este artículo proponemos un nuevo modelo de regresión con efectos mixtos para variables acotadas fraccionarias. Este modelo nos permite incorporar covariables directamente al valor esperado, de manera que podemos cuantficar exactamente la influencia de estas covariables en la media de la variable de interés en vez de en la media condicional. La estimación se llevó a cabo desde una perspectiva bayesiana y debido a la complejidad de la distribución aumentada a posteriori usamos un algoritmo de Monte Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Fernandez et al [6] propose a mixed effects regression model for fractional bounded response variables that allows the incorporation of covariates directly to the expected value so that their influence in the mean of the variable of interest, rather than on the conditional mean, can be exactly quantified. Their estimation was carried out from a Bayesian perspective and the Monte Carlo simulations showed that the proposed model outperforms other traditional longitudinal models for bounded variables Vallejos et al [7] provide mathematical properties of the effective geographic sample size defined in [8], including the mathematical support that enhances the use of this definition in practice, the establishment of the asymptotic normality of maximum likelihood for the effective sample size, and the definition of hypothesis testing for the effective sample size.…”
mentioning
confidence: 99%
“…Fernandez et al [6] propose a mixed effects regression model for fractional bounded response variables that allows the incorporation of covariates directly to the expected value so that their influence in the mean of the variable of interest, rather than on the conditional mean, can be exactly quantified. Their estimation was carried out from a Bayesian perspective and the Monte Carlo simulations showed that the proposed model outperforms other traditional longitudinal models for bounded variables Vallejos et al [7] provide mathematical properties of the effective geographic sample size defined in [8], including the mathematical support that enhances the use of this definition in practice, the establishment of the asymptotic normality of maximum likelihood for the effective sample size, and the definition of hypothesis testing for the effective sample size.…”
mentioning
confidence: 99%